Dialect Continum in Padawan: Differences of Bidayuh Biatah in Kampung Quop, Kampung Mambong and Kampung Benuk - Augustin, Alexander (Hunatech Vol. XXX, No. XXX, 2024)
This study was conducted to see if the dialect continum phenomenon is also present happened in Sarawak. The language that is the focus of the study is the Bidayuh language, especially the Bidayuh Biatah dialect and subdialects spoken in  the Padawan area, Sarawak. The research methodology that has been used  in  this study is, research field by interviewing 12 informants from three villages which are different, as well as corpus data, by using a word list book. This study will analyze and discuss the differences in terms of semantics ie focusing on synonyms, hyponyms, as well as homophones and phonological differences that is, focusing on the dropping and diftongong found in each village This research has indirectly proved and supports the opinion of how the distance factor plays an important role which causes the  emergence of many dialects and subdialects in a language.